Ethics and Economics of the COVID-19 Pandemic in the United States - Hilsenrath, Peter (Health Serv Res Manag Epidemiol, 2020)
The Covid-19 experience provides a natural experiment in personal and social ethics. Difficult decisions are routinely made to optimize lives and livelihoods. This commentary provides background and insight into the ethical and economic foundations underpinning dilemmas of this historic pandemic.